Interview with Professor Philippe Denis - Helené van Tonder (Acta Theologica)
From text: Prof. Philippe Denis is a Senior Professor in History of Christianity at the University of Kwazulu?Natal. In the 1970s and 1980s, his research focused on the history of the Reformation in Germany, France and The Netherlands, and specifically on issues of confessional development, biblical exegesis, and cultural representations. Over the past two decades, his research focused primarily on the history of indigenous Christianity in southern Africa, along with an interest in oral history.